Sex crime: [sex offending and society] - Thomas, Terry (Routledge, 2016)
Introduction -- The sex offender "problem" and responses -- Social responses to the sex offender : a historical perspective -- Policing sexual offending -- The search for justice : the sex offender in court -- The search for justice : punishing the sex offender -- The victims of sexual offending -- Protection in the home -- Protection in the community -- Conclusions